2014
DOI: 10.1128/aem.03844-13
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Sequence-Based Types of Legionella pneumophila Serogroup 1 Strains Isolated from Cooling Towers, Hot Springs, and Potable Water Systems in China

Abstract: bLegionella pneumophila serogroup 1 causes Legionnaires' disease. Water systems contaminated with Legionella are the implicated sources of Legionnaires' disease. This study analyzed L. pneumophila serogroup 1 strains in China using sequence-based typing. Strains were isolated from cooling towers (n ‫؍‬ 96), hot springs (n ‫؍‬ 42), and potable water systems (n ‫؍‬ 26). Isolates from cooling towers, hot springs, and potable water systems were divided into 25 sequence types (STs; index of discrimination [IOD], 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 32 publications
3
33
1
Order By: Relevance
“…The IOD of environmental isolates in our investigation (0.950) is higher than that previously reported in China (0.749) (Qin et al, 2014), Japan (0.886) (Amemura-Maekawa et al, 2012), Canada (0.888) (Reimer et al, 2010) and United States (0.822) (Kozak et al, 2009), and slightly lower than United Kingdom (0.954) (Harrison et al, 2009) and Singapore (0.970) (Lim et al, 2011). Taking the small sampling area of this study (two cities) into account, we speculated a higher genetic diversity of L. pneumophila isolates in our study.…”
Section: Pneumophila Sequence-based Typingcontrasting
confidence: 77%
“…The IOD of environmental isolates in our investigation (0.950) is higher than that previously reported in China (0.749) (Qin et al, 2014), Japan (0.886) (Amemura-Maekawa et al, 2012), Canada (0.888) (Reimer et al, 2010) and United States (0.822) (Kozak et al, 2009), and slightly lower than United Kingdom (0.954) (Harrison et al, 2009) and Singapore (0.970) (Lim et al, 2011). Taking the small sampling area of this study (two cities) into account, we speculated a higher genetic diversity of L. pneumophila isolates in our study.…”
Section: Pneumophila Sequence-based Typingcontrasting
confidence: 77%
“…This species includes 15 polyclonal serogroups (SGs). Most of the clinical isolates represent SG1, which is present worldwide and is also the most commonly cultured SG from environmental samples (6,7,8,9,10,11). The use of monoclonal antibodies (MAbs) revealed more heterogeneity in L. pneumophila, and nine phenons reacting with different MAbs have been defined within SG1 (12).…”
mentioning
confidence: 99%
“…Similarly, another study conducted in Canada obtained the same result that locus mompS provided the most alleles (22). However, one study on SBT of L. pneumophila strains in mainland China indicated that mip and flaA individually provided the most alleles in the isolates from cooling water and hot spring water (19). This might be attributed to the geographical correlation which could lead to the emergence of these results.…”
Section: Discussionmentioning
confidence: 64%
“…In one study conducted in England and Wales, ST1 was the most frequent STs, accounting for 35% of the number of L. pneumophila environmental isolates (18). From the L. pneumophila serogroup 1 isolates from potable systems, cooling towers, and hot springs in China, ST1 were reported to be about 14.3%, to 53.1% and 92.3%, respectively (19). For L. pneumophila strains, ST1 (1, 4, 3, 1, 1, 1) is predominant in environmental samples, widely distributed around world (18,20,21).…”
Section: Discussionmentioning
confidence: 99%